Effects of plyometric jump training in female soccer player's vertical jump height: A systematic review with meta-analysis. Issue 13 (2nd July 2020) - Ramirez-Campillo, Rodrigo; Sanchez-Sanchez, Javier; Romero-Moraleda, Blanca; Yanci, Javier; García-Hermoso, Antonio; Manuel Clemente, Filipe
ABSTRACT: To assess the effects of plyometric jump training (PJT) in female soccer player's vertical jump height, a review was conducted using the data sources PubMed, MEDLINE, Web Of Science and SCOPUS. Only peer-review articles were included. To qualify for inclusion in the meta-analysis, studies must have included (i) a PJT programme of at least 2 weeks, (ii) cohorts of healthy female soccer players with no restriction for age, (iii) a control group, (iv) a measure of countermovement jump (CMJ). The inverse variance random-effects model for meta-analyses was used. From 7, 136 records initially identified through database searching, 8 were eligible for meta-analysis, comprising 9 training groups (n = 99) and 9 control groups (n = 94). The magnitude of the main effect was moderate (ES = 1.01 [95%CI = 0.36–1.66], Z = 3.04, p = 0.002). Sub-group analyses were performed (i.e., PJT frequency, duration and total number of sessions), revealing no significant subgroup differences (p = 0.34–0.96). Among the studies included in this review, none reported injury or other adverse effects. In conclusion, PJT is effective in female soccer players for the improvement of vertical jump height. In future, research must identify specific dose–response relationships following PJT, particularly in the long term.